Adsorptive remediation of naproxen from water using in-house developed hybrid material functionalized with iron oxide - Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (2022)
Every year, a considerable volume of medications is consumed. Because these medications are not entirely eliminated in the sewage treatment plants and impact the surface waterways, the environmental pollution problem arises. This study objective was to evaluate the possibility of using an absorbent material made with of polyethylene terephthalate and sugarcane bagasse ash functionalized with iron oxide (PETSCA/Fe3+) in the removal of naproxen from water. The feasibility of having viable features in becoming an efficient adsorbent was first determined. The batch test was performed, allowing the dose effect, adsorption kinetics, and isotherm models to be evaluated. The determination of naproxen (NAP) concentration in water was analyzed on a high-performance liquid chromatograph and Langmuir method best represented the adsorption isotherm model. PETSCA/Fe3+ adsorbent material demonstrated potential in the naproxen removal at a low cost. The batching process was satisfactory, with 0.30 g of composite being the optimum fit for the system. The adsorption kinetics was determined and described by the pseudo second order model, with an average correlation coefficient (R2) of 0.974. The adsorption system model was best represented by the Langmuir isotherm curve. Moreover, adsorption in the presence of H2O2 had a positive impact on the process, removing 81.9% of NAP, whereas the process without H2O2 did not remove more than 62.0% of NAP. Therefore, because of its good qualities for NAP removal, PETSCA/Fe3+ is recommended as adsorbent material, primarily in small-volume water filtration systems.